Inhibiting AKT Phosphorylation Employing Non-Cytotoxic Anthraquinones Ameliorates T(H)2 Mediated Allergic Airways Disease and Rhinovirus Exacerbation - Cesar de Souza Alves, Caio (Public Library of Science, 2013)
BACKGROUND: Severe asthma is associated with T helper (T(H)) 2 and 17 cell activation, airway neutrophilia and phosphoinositide-3-kinase (PI3K) activation. Asthma exacerbations are commonly caused by rhinovirus (RV) and also associated with PI3K-driven inflammation. Anthraquinone derivatives have been shown to reduce PI3K-mediated AKT phosphorylation in-vitro. OBJECTIVE: To determine the anti-inflammatory potential of anthraquinones in-vivo. METHODS: BALB/c mice were sensitized and challenged with crude house dust mite extract to induce allergic airways disease and treated with mitoxantrone and a novel non-cytotoxic anthraquinone derivative. Allergic mice were also infected with RV1B to induce an exacerbation. RESULTS: Anthraquinone treatment reduced AKT phosphorylation, hypoxia-inducible factor-1α and vascular endothelial growth factor expression, and ameliorated allergen- and RV-induced airways hyprereactivity, neutrophilic and eosinophilic inflammation, cytokine/chemokine expression, mucus hypersecretion, and expression of T(H)2 proteins in the airways. Anthraquinones also boosted type 1 interferon responses and limited RV replication in the lung. CONCLUSION: Non-cytotoxic anthraquinone derivatives may be of therapeutic benefit for the treatment of severe and RV-induced asthma by blocking pro-inflammatory pathways regulated by PI3K/AKT.